The Effect of Teaching Model and Students' Personalities on Students’ Learning Achievement - Charli, Leo; Sukardjo, Moch.; Muslim, Suyitno (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
This article aimed at illustrating how students’ personalities (introvert and extrovert) affects their learning outcomes of chemistry subject when the teacher employs two learning models, i.e. inside-outside circle and snowball throwing. This research uses quantitative approach, particularly quasi experiment. The result of the research showed that the learning outcomes of chemistry by extrovert students were higher when using inside-outside circle learning model compared to snowball throwing. On the other hand, the learning outcomes of introvert students who studied chemistry were higher when using snowball throwing learning model compared to inside-outside circle. The finding of this research that shows the learning outcomes differences regarding students’ personalities are interesting to be considered by the teachers in selecting and developing learning activities in classroom to improve the students’ learning outcomes optimally. Abstrak Artikel ini bertujuan untuk menggambarkan bagaimana pengaruh kepribadian siswa (introvert dan ekstrovert) terhadap hasil belajar mata pelajaran Kimia di antara dua model pembelajaran, yaitu inside-outside circle dan snowball throwing. Penelitian ini berpendekatan kuantitatif dan menggunakan kuasi eksperimen semu. Hasil penelitian ini menunjukkan bahwa hasil belajar Kimia dari siswa dengan kepribadian ekstrovert ketika menggunakan model pembelajaran inside-outside circle lebih tinggi dibanding ketika menggunakan model pembelajaran snowball throwing. Di sisi lain, siswa yang berkepribadian introvert ketika menggunakan model pembelajaran snowball throwing hasil belajarnya lebih tinggi dibandingkan ketika menggunakan model pembelajaran inside-outside circle. Temuan yang menunjukkan perbedaan hasil belajar dilihat dari faktor kepribadian ini menarik sebagai pertimbangan guru dalam memilih dan mengembangkan pembelajaran di kelas agar hasil belajarnya lebih optimal.